ADVENTURE-BASED LEARNING IN PHYSICAL EDUCATION: A TRANSFORMATIONAL MODEL FOR CHARACTER BUILDING AND TEAMWORK - Andi Gunawan (Journal of Physical Education, Health and Sports Recreation, 2025)
This study aims to analyze the implementation of the Adventure-Based Learning model in Physical Education and assess its impact on character development and teamwork among junior high school students in Sidoarjo Regency. Using a descriptive qualitative approach with a case study method, data were collected through participant observation, in-depth interviews, and documentation at SMP Negeri 1 Sidoarjo. The results indicate that the ABL model positively contributes to character development, including responsibility, courage, honesty, and independence. Furthermore, ABL also improves teamwork, communication, and empathy among students. Despite challenges such as limited facilities and the need for teacher training, this model received a positive response from students and teachers. In conclusion, adventure-based learning is a relevant, transformative approach to be integrated into the Physical Education curriculum to holistically shape students' character.